Taste of Tucson : Sonoran-style recipes inspired by the rich culture of Southern Arizona - Alpers, Jackie (West Margin Press, 2020)
A collection of delicious recipes from local restaurant experts and the author's own original recipes, all inspired by the rich culture of Sonora, Arizona. A cookbook dedicated to the foods inspired by the region's beauty and diversity, Taste of Tucson discovers through recipes and photos the unique mix of cultures that create Southern Arizona's incredible cuisine. Award-winning photographer and cookbook author Jackie Alpers shares her own inspired food creations in this book as well as her favorite restaurants' dishes, while incorporating the history of the Sonora region, the mysticism and lore, and how it has contributed to the food of the people who live there. Building from tried-and-true basics and tutorials on tacos, enchiladas, carne asada, and huevos rancheros, she divulges secrets to making Sonora's most unique savories and sweets, including Chicken Mole Amarillo, Adobo Pulled Pork, Red Pozole, Dark Chocolate and Coffee Figgy Pudding Cakes, and more.For cooks of all levels, from anywhere in the world who loves to dine on this Southwestern region's foods, this cookbook welcomes you to bring Sonora's best and most iconic tastes into your own kitchen.